Brexit, the left behind and the let down: the political abstraction of 'the economy' and the UK's EU referendum. Issue 1 (April 2018) - Watson, Matthew
Abstract UK voters' decision to overturn the country's European Union membership has left most parliamentarians looking rather distant from the constituents they represent. The politicians staked much on assuming that people could be persuaded not to sabotage their economic self-interest, but that message conspicuously failed to resonate. When politicians spoke in abstract terms about the needs of 'the economy', significant numbers understood this to mean labour market conditions that had personally served them badly. It was commonplace in the immediate aftermath of the referendum to refer to these people as the 'left behind'. However, they might more usefully be described as the 'let down' and, as the 2017 general election results show, they are still a significant if somewhat unpredictable voting constituency. Since the restructuring of the UK economy in line with global competitiveness norms these people have been required to earn their rights as citizens through demonstrating their work readiness. Yet hard work on its own is now no longer sufficient for so many people to receive the rewards promised under the terms of the new social contract. They have been largely abandoned to their fate by the politicians as labour market segmentation has led to a significant expansion of the in-work poor. This constituency voted in large numbers against continued EU membership. This suggests that the referendum result can be seen at least in part as a revolt against the way in which the abstraction of 'the economy' has informed UK politics in recent decades. The much lower profile given to this abstraction at the 2017 general election compared to its immediate predecessors indicates that, eighteen months later, on this issue at least we remain in the political rupture caused by the EU referendum result.